Evaluating the Genetic Capacity of Mycoplasmas for Coenzyme A Biosynthesis in a Search for New Anti-mycoplasma Targets - Ras, Tertius Alwyn; Strauss, Erick; Botes, Annelise (Frontiers in Microbiology, 2021)
Mycoplasmas are responsible for a wide range of disease states in both humans and animals in which their parasitic lifestyle has allowed them to reduce their genome sizes and curtail their biosynthetic capabilities. The subsequent dependence on their host offers a unique opportunity to explore pathways for obtaining and producing cofactors—such as coenzyme A (CoA)—as possible targets for the development of new anti-mycoplasma agents. CoA plays an essential role in energy and fatty acid metabolism and is required for membrane synthesis. However, our current lack of knowledge of the relevance and importance of the CoA biosynthesis pathway in mycoplasmas, and whether it could be bypassed within their pathogenic context, prevents further exploration of the potential of this pathway. In the universal, canonical CoA biosynthesis pathway, five enzymes are responsible for the production of CoA. Given the inconsistent presence of the genes that code for these enzymes across mycoplasma genomes, this study set out to establish the genetic capacity of mycoplasmas to synthesize their own CoA de novo. Existing functional annotations and sequence, family, motif and domain analysis of protein products were used to determine the existence of relevant genes in mycoplasma genomes. We found that most Mycoplasma species do have the genetic capacity to synthesize CoA, but there was a differentiated prevalence of these genes across species. Phylogenetic analysis indicated that the phylogenetic position of a species could not be used to predict its enzyme-encoding gene combinations. Despite this, the final enzyme in the biosynthesis pathway—dephospho-coenzyme A kinase—was found to be the most common amongst the studied species, suggesting that it has the most potential as a target in the search for new broad-spectrum anti-mycoplasma agents.